Interfering B cell receptor signaling via SHP-1/p-Lyn axis shows therapeutic potential in diffuse large B-cell lymphoma - Ji-Lin Chen; Pei-Yi Chu; Chun-Teng Huang; Tzu-Ting Huang; Wan-Lun Wang; Yu-Hsuan Lee; Yuan-Ya Chang; Ming-Shen Dai; Chung-Wai Shiau; Chun-Yu Liu (BMC, 2022)
Abstract Background Diffuse large B cell lymphoma (DLBCL) is an aggressive and molecularly heterogeneous non-Hodgkin's lymphoma. The B cell receptor (BCR) signaling pathway in DLBCL emerges as a new drug target. Protein phosphatase SHP-1 negatively regulates several oncogenic tyrosine kinases and plays a tumor suppressive role. Methods The direct SHP-1 agonists were used to evaluate the potential therapeutic implication of SHP-1 in DLBCL. Immunohistochemical staining for SHP-1 was quantified by H-score. The SHP-1 phosphatase activity was determined using tyrosine phosphatase assay. In vitro studies, including MTT, western blot analysis and cell apoptosis, were utilized to examined biological functions of SHP-1. Results Oral administration of SHP-1 agonist showed the potent anti-tumor effects compared to a selective Bruton's tyrosine kinase (BTK) inhibitor ibrutinib in mice bearing U2932 xenografts. SHP-1 agonist increased SHP-1 activity as well as downregulated p-Lyn in vivo. Here, we demonstrated that immunohistochemical staining for SHP-1 expression was positive in 76% of DLBCL samples. SHP-1 agonist exerted anti-proliferative and apoptotic effects compared with ibrutinib in DLBCL cells. Mechanistically, SHP-1 agonist decreased BCR signaling, especially p-Lyn, and led to apoptosis. Conclusions These data suggest that SHP-1 negatively regulates phosphorylation of Lyn, and targeting SHP-1/p-Lyn using SHP-1 agonist has therapeutic potential for treatment of DLBCL.